Assessment of fatigue resistance of additivated asphalt concrete incorporating fibers and polymers - Brovelli, Claudio (2014)
This paper reports the evaluation of fatigue response of asphalt mixtures produced with different additives, namely cellulose and synthetic fibers, amorphous polyolefin, Ethyl Vinyl Acetate (EVA) in comparison with conventional asphalt mixtures. The additive content was also analyzed by producing asphalt mixtures with 3, 6 and 9% of additive. Fatigue testing was performed with an indirect tensile test apparatus under controlled stress mode of loading. A comparing analysis of the fatigue resistance within different methods was carried out. Fatigue life was defined using the classical approach in which the number of cycles reaches the double of initial deformation. It was also defined in terms of different methods based on dissipated energy: total dissipated energy, ratio of dissipated energy change and plateau value. This paper offers an analysis of different methods of evaluating the indirect tensile fatigue test. The testing conducted clearly shows that polymer modification may extend the fatigue life and that energetic methods can be effectively applied to data from indirect tensile fatigue tests.